2022
DOI: 10.3390/jcm11051295
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two 3D-Printed Indirect Bonding (IDB) Tray Design Versions and Their Influence on the Transfer Accuracy

Abstract: Objective: This study aims to investigate the transfer accuracy of two different design versions for 3D-printed indirect bonding (IDB) trays. Materials and Methods: Digital plaster models of 27 patients virtually received vestibular attachments on every tooth using OnyxCeph³™ (Image Instruments, Chemnitz, Germany). Based on these simulated bracket and tube positions, two versions of transfer trays were designed for each dental arch and patient, which differed in the mechanism of bracket retention: Variant one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
0
11
0
2
Order By: Relevance
“…The transversal direction was less deviated in the incisors and most obvious in canines and premolars. Errors in premolars may be caused by the teeth being located at the back of the mouth, which has limited operating space [ 8 , 18 , 36 ]. Whereas the errors in canines are usually caused by their convex surface and limited bonding range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transversal direction was less deviated in the incisors and most obvious in canines and premolars. Errors in premolars may be caused by the teeth being located at the back of the mouth, which has limited operating space [ 8 , 18 , 36 ]. Whereas the errors in canines are usually caused by their convex surface and limited bonding range.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3D printing technology can design trays with different structures to meet the treatment needs of orthodontic patients [ 9 , 10 , 15 17 ]. Von et al [ 18 ]. designed two different IDB transfer trays via 3D printing technology and validated the good accuracy and comparability of the two trays for clinical use, but did not involve adhesive.Shin et al [ 19 ] demonstrated that 3D-printed indirect bonding tray has a slightly superior bracket placement accuracy than conventional methods, but it doesn’t improve bracket positioning accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on its flexibility, the IBT resin could be successfully used as a tray for indirect bracket placement, although our research showed that it should not be used to prepare more stable and precise products, such as surgical guides [ 16 , 25 ]. For an indirect bonding tray, this kind of resin shows sufficient accuracy and low linear and angular deviations, which provides good reflection in the final bracket and/or attachment bonding [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2012) en la que indica que la delimitación del acondicionamiento ácido únicamente donde irá cementado el aparato ortodóncico reduce la acumulación de placa alrededor de los mismos. 5 Si bien es cierto que se ha utilizado la sobreimposición digital de escaneos, 4,11 estas técnicas incluyen todo el flujo de trabajo digital, lo cual consideramos una limitación aún en muchos países de la región debido a su elevado costo; por lo tanto, en esta técnica propuesta, se decidió incluir pasos análogos que, sin embargo, con el escaneo digital final, demuestran una alta precisión en la transferencia de los brackets desde los modelos de trabajo hasta su ubicación definitiva en la boca del paciente.…”
Section: Discussionunclassified
“…3 La técnica indirecta de cementación de aparatos ortodóncicos fijos fue propuesta por primera vez en 1972 por Silverman et al con el objetivo de reducir los errores en el posicionamiento, lo que significaba consecuencias negativas y tener que reubicarlos en algún momento del tratamiento. 4 Desde entonces, se ha propuesto diferentes métodos de transferencia desde los modelos donde inicialmente se colocan los brackets para luego ser llevados a la boca del paciente. [5][6] Entre los métodos de transferencia, se han descrito algunos con láminas termoplásticas, polivinil siloxanos, 7 y más recientemente se ha incluido la tecnología CAD/CAM para elaborar guías buscando una mayor precisión.…”
Section: Introductionunclassified